2020
DOI: 10.1038/s41422-019-0267-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of γ-globin expression through Cas9 or base editor to treat β-hemoglobinopathies

Abstract: z Dear Editor, Mutations in the β-globin gene, the essential component of adult hemoglobin (HbA; α2β2), results in either a production of aberrant sickle hemoglobin (HbS) leading to sickle cell disease (SCD) or an insufficient β-globin synthesis leading to β-thalassemia. These two major forms of β-hemoglobinopathies cause impaired erythropoiesis and life-threatening anemia. Clinical evidence has suggested that reactivation of fetal γ-globin (HBG) gene expression which is normally silenced after birth by certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…Currently, adeno-associated virus (AAV), the most promising in vivo delivery vector, is being combined with genome-editing tools to treat various genetic disorders. [13][14][15][16][17] Therefore, we hypothesized that disrupting LDH via the CRISPR/Cas9 system may present a better alternative treatment for patients with PH1 because of its permanent effect and the fact that a complete elimination of LDH is not required for the treatment of PH1.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, adeno-associated virus (AAV), the most promising in vivo delivery vector, is being combined with genome-editing tools to treat various genetic disorders. [13][14][15][16][17] Therefore, we hypothesized that disrupting LDH via the CRISPR/Cas9 system may present a better alternative treatment for patients with PH1 because of its permanent effect and the fact that a complete elimination of LDH is not required for the treatment of PH1.…”
Section: Introductionmentioning
confidence: 99%
“…These nanopores allowed local electric field upon low-voltage and resulted in a small number of nanochannels on the cell membrane with efficient RNP delivery into both suspension and adherent cells (Figure 2 C). It is worth noting that enhancing sgRNA stability by chemical modification can further improve the genome editing efficiency of electroporation-mediated RNP delivery 96 , 97 .…”
Section: Physical Approaches For Rnp Deliverymentioning
confidence: 99%
“…The author concluded that 10% or more expression of the exogenous normal β-globin gene was capable of reducing the degree of anemia in their β-thalassemia mouse model [29]. Recently, Wang et al reactivated the expression of γ-globin using RNPs of Cas9 and base editor to modify the hemoglobin subunit gamma (HBG) promoter region mimicking the effect of naturally occurring Δ13 bp allele in patients with hereditary persistence of fetal hemoglobin [34].…”
Section: β-Thalassemiamentioning
confidence: 99%